Health promotion and screening in elderly congregate of PCM (Pimpinan Cabang Muhammadiyah) north Banguntapan to improve quality of life - Nisa, Afifah Khoiru; Ariani, Rizka; Aristiani, Windy; Rizkita, Leonny Dwi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2024)
Common non-communicable disease such as hypertension or diabetes mellitus is often found in elderly. Irregular medical check-up and uncontrolled medicine could lead into complications such as stroke and kidney failure. Elderly is also considered vulnerable and fragile, thus memory disturbance also sometimes occurs. Although these problems are inevitable due to ageing process, many strategies can be applied to prevent to complications. For example, by giving regular check-ups and knowledge transfer through health promotion, as well as early screenings. Thus, the aims for the community service are increasing the elderly’s understanding, forming proactive elderly and providing laboratory screenings. The method used is interactive presentation about non-communicable disease, medical check-ups for blood glucose, uric acid and total cholesterol level, and memory to quality of life assessment for elderly. The target of this service is elderly congregate of Jihad (Pengajian Ahad) Pagi of PCM (Pimpinan Cabang Muhammadiyah) North Banguntapan, Bantul Regency, DIY (Daerah Istimewa Yogyakarta). The result of the implementation of the service activity is increasing knowledge and awareness in regards of non-communicable and mental disease in elderly, as well as medical screenings data for next service project.